2019
DOI: 10.21873/anticanres.13629
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Colorectal Cancer Patients Treated With Combination of Immune-cell Therapy and First-line Chemotherapy: A Retrospective Study

Abstract: chemotherapy and immune-cell therapy (17-19). However, the efficacy and prognostic factors of immune-cell therapy combined with 1st-line chemotherapy in a large number of patients with CRC remain unclear. In this study, we retrospectively analyzed patients with advanced CRC who had been administered immune-cell therapy as the 1st-line setting at the clinics of the Seta Clinic Group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The combination of chemotherapeutic agents, such as cisplatin, with ACT has been reported to improve the survival time of patients with cervical cancer (17). In the comparison between immune-cell therapy alone and immune-cell therapy combined with other treatments, several studies have demonstrated that combination therapy shows better therapeutic effects than immune-cell therapy alone (16,(18)(19)(20)(21). In our study, the combination of immune-cell therapy and chemotherapy did not provide any survival benefit for advanced or recurrent endometrial and cervical cancer patients, although the MST of these patients treated with a combination of immune-cell therapy and chemotherapy was longer than that of the historical control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of chemotherapeutic agents, such as cisplatin, with ACT has been reported to improve the survival time of patients with cervical cancer (17). In the comparison between immune-cell therapy alone and immune-cell therapy combined with other treatments, several studies have demonstrated that combination therapy shows better therapeutic effects than immune-cell therapy alone (16,(18)(19)(20)(21). In our study, the combination of immune-cell therapy and chemotherapy did not provide any survival benefit for advanced or recurrent endometrial and cervical cancer patients, although the MST of these patients treated with a combination of immune-cell therapy and chemotherapy was longer than that of the historical control.…”
Section: Discussionmentioning
confidence: 99%
“…Adoptive immune-cell therapy is still under evaluation for use in advanced endometrial cancer, as in many other malignancies (16,20,21), but the more mature data available are about the checkpoint inhibitors. The PD-L1 expression levels in endometrial cancer have been estimated to be 67-100% (23).…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most commonly detected cancer with 1.8 million cases worldwide in 2018 [1][2][3]. Currently, conventional treatments for CRC include surgical removal of tumors, radiation therapy, and chemotherapy [4]. Despite advances in these treatments, CRC has shown resistance to these treatments alone [5].…”
Section: Introductionmentioning
confidence: 99%
“…as a combination between chemotherapy and immunotherapy, has been developed as a more powerful anticancer therapy. Accumulating evidence sheds light on chemoimmunotherapy using adoptive T cell transfusions as a useful mCRC therapy (19)(20)(21)(22). Previously, we showed that chemoimmunotherapy using αβ T cells was feasible and safe in stage IV CRC (22,23).…”
mentioning
confidence: 99%